The Limits of Centralized Pricing in Online Marketplaces and the Value of User Control - Filippas, Apostolos; Jagabathula, Srikanth; Sundararajan, Arun (Management Science, 2023)
We report experimental and quasi-experimental evidence from a “sharing economy” marketplace that transitioned from decentralized to centralized pricing. Centralized pricing increased the utilization of providers’ assets, resulting in higher revenues but also higher transaction costs. Providers who were barred from accessing the price system made nonprice adjustments, including reducing the availability of their assets, canceling booked transactions, and exiting the market. Providers who retained partial pricing control reacted substantially less but experienced similar revenue increases. We highlight the challenges of implementing centralized pricing and assessing its welfare effects. We show that partial control can mitigate these challenges, allowing providers to express their private and heterogeneous preferences while maintaining the benefits of centralization. This paper was accepted by Gabriel Weintraub, revenue management and market analytics. Funding: S. Jagabathula was funded in part by the Division of Civil, Mechanical, and Manufacturing Innovation [Grant 1454310]. Supplemental Material: The data files and online appendices are available at https://doi.org/10.1287/mnsc.2023.4789 .